Immunostaining of Bcl-2 and HER2/neu in urinary bladder carcinoma. Issue 1 (July 2016) - Mohamed, Said Abu-Alkhair
Abstract : Background: Bladder cancer is one of the most common malignancies and a major cause of cancer morbidity and mortality. Bcl-2 family, a group of closely related proteins, plays a major regulatory role in apoptosis. The human epidermal growth factor receptor 2/neu ( HER2/neu ) gene is located on the chromosomal region 17q12. It encodes a transmembrane glycoprotein that belongs to the EGF/erbB growth factor receptor family. Aim: The aim of the present study was to determine the significance of bcl-2 and HER2/neu expression in patients with urinary bladder carcinomas in correlation with the histopathological parameters. Materials and methods: Forty-five fixed, paraffin-embedded paired tissue sections from bladder carcinomas were studied for the expression of both Bcl-2 and HER2/neu by using immunohistochemistry. Results: There was a significant correlation between Bcl-2 immunoreactivity and low-grade tumor; Bcl-2 also significantly associated with early tumor stages. In addition, there were statistically significant relationships between pathological grade, tumor stage, and HER2/neu . Conclusion: Expression of Bcl-2 in the bladder carcinoma seems to be associated with a less aggressive phenotype and does not play an important role in tumour progression. These findings support the role of HER2/neu in the carcinogenesis of urinary bladder carcinoma regarding behavior and aggressiveness, and thus HER2/neu could be considered as a poor prognostic parameter in urinary bladder carcinoma.